Political Discourse and Discursive Practices of Political Parties on Contemporary Electoral Fields in Surat Thani Province - Tatisunthon, Thanisorn; Lapi-e and, Aussiri; Puakkong, Chaiwat (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
The objectives of this research article were 1) to study the formation of political ideology among the Democratic Party. and, Palang Pracharath Party in the Contemporary Context Area 1, Surat Thani Province; and 2) to Propos forms of discourse and discourse operations through political parties in the contemporary context Area 1, Surat Thani Province. It is a qualitative research. Data were collected from the survey of relevant literature documents. Moreover, detailed data insights were collected from eight people was chosen using a purposive sampling method. The data were presented in a descriptive analysis. The results of the study indicated that 1) political ideology formation between the Democratic Party and the Palang Pracharath Party discovered that the Democratic Party has a liberal-classical ideology that leans conservative. While the Pracharat Party maintains state interests through a liberal economic ideology. 2) proposing a type of discourse and political party discourse was discovered that the presence of a political party under the condition of support connects the phenomenon via a political actor in three forms: 1) expanding the state’s ideological mechanism, 2) resisting state ideological mechanism expansion, and 3) expanding the state’s ideological mechanism through alternative networks. Such circumstances may reflect political struggles that reproduce the discourses of traditional ideological sets. When considering the future trend, the party is more important than the individual, creating a space for political actors through the opposing party. This is expected to lead to the establishment of new political parties in the area. It is a new kind of struggle for popularity phenomenon that clearly extends contemporary ideology.